Pemberdayaan Hukum Ibu dalam Pemenuhan Hak ASI Anak sebagai Upaya Pencegahan Stunting dan Penyakit Jantung: Empowering Mothers Through the Law to Ensure Children’s Right to Breastfeeding as a Measure to Prevent Stunting and Heart Disease - Dewi Septiana; Dewi Sartika; Nur Kholis (Jurnal Dedikasi Hukum, 2025)
The prevalence of stunting reaches 150.8 million children worldwide, and one strategy for preventing stunting can be implemented through exclusive breastfeeding. According to the law, exclusive breastfeeding is an obligation for every mother, but its implementation shows that exclusive breastfeeding rates remain low in various regions. This community service aims to increase mothers' knowledge and awareness about the obligation of exclusive breastfeeding to prevent stunting and heart disease. This activity was conducted with 22 participants (pregnant women, breastfeeding mothers, and mothers with infants) who were purposively selected. Education was provided through multimedia presentations and educational booklets that covered the legal, religious, and medical aspects of breastfeeding, accompanied by demonstrations of breastfeeding practices and health examinations. Knowledge levels were measured before and after the intervention, while anthropometric and clinical data were collected during medical examinations. The analysis used cross-tabulation. Results showed a significant increase in knowledge of 63%, with participants scoring high (>76) increasing from 23% to 86%, while those with low knowledge (<56) decreased from 50% to 5%. A clinical evaluation of 19 willing participants revealed an average height of 155 cm, a weight of 58.4 kg, a blood pressure of 118 mmHg, a cholesterol level of 205 mg/dL (exceeding the normal range), and a glucose level of 103 mg/dL. This integrated program effectively strengthened mothers' understanding and commitment to exclusive breastfeeding, supporting stunting prevention and maternal cardiovascular health. This holistic approach combining legal, religious, and health perspectives serves as a model for community-based breastfeeding promotion programs. Abstrak Prevalensi angka stunting mencapai 150,8 juta pada anak di seluruh dunia, salah satu strategi pencegahan stunting dapat dilakukan dengan pemberian ASI eksklusif. Pemberian ASI ekslusif menurut Undang-undang adalah kewajiban bagi tiap ibu, namun implementasinya menunjukkan angka pemberian ASI ekslusif masih rendah di berbagai wilayah. Pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan dan kesadaran ibu tentang kewajiban ASI ekslusif untuk mencegah stunting dan penyakit jantung. Kegiatan ini dilakukan pada 22 peserta (ibu hamil, menyusui, dan ibu dengan bayi) yang dipilih secara purposif. Edukasi dilakukan menggunakan presentasi multimedia dan booklet edukatif mencakup aspek hukum, agama, dan medis tentang ASI, disertai demonstrasi praktik menyusui dan pemeriksaan kesehatan. Tingkat pengetahuan diukur sebelum dan sesudah intervensi, sedangkan data antropometrik dan klinis dikumpulkan saat pemeriksaan medis. Analisis menggunakan tabulasi silang. Hasil menunjukkan peningkatan pengetahuan signifikan sebesar 63%, dengan peserta berskor tinggi (>76) meningkat dari 23% menjadi 86%, sementara yang berpengetahuan rendah (<56) menurun dari 50% menjadi 5%. Evaluasi klinis pada 19 peserta yang bersedia menunjukkan rata-rata tinggi badan 155 cm, berat badan 58,4 kg, tekanan darah 118 mmHg, kolesterol 205 mg/dL (melebihi normal), dan glukosa 103 mg/dL. Program kegiatan terintegrasi ini efektif memperkuat pemahaman dan komitmen ibu terhadap ASI eksklusif, mendukung pencegahan stunting dan kesehatan kardiovaskular ibu. Pendekatan holistik yang menggabungkan perspektif hukum, agama, dan kesehatan ini menjadi model untuk program promosi menyusui berbasis komunitas.